Shear band control for improved strength-ductility synergy in metallic glasses - Sha, Zhendong (2023)
Aside from ultrahigh strength and elasticity, metallic glasses (MGs) possess a number of favorable properties. However, their lack of dislocation based plastic deformation mechanisms in crystalline metals and the resulting loss of ductility have restricted the engineering applications of MGs over the last 60 years. This review aims to provide an overview of deformation and failure mechanisms of MGs via formation and propagation of shear bands (SBs), with an emphasis on the control of SBs to promote strength-ductility synergy. With this goal in mind, we highlight some of the emerging strategies to improve the ductility of MGs. Topics covered include postprocessing techniques such as precompression, heterogeneity tuning, and rejuvenation, with a primary focus on recent progresses in structural design based methods including nanoglasses, notched MGs, and MG nanolattices, as future innovations toward strength-ductility synergy beyond the current benchmark ranges.